The Success Of The Country In Resolving The Sunning Of KRI Nanggala 402 (International Journal of Scientific Research and Management (IJSRM), 2022)
A year of remembering the sinking of KRI Nanggala 402 still leaves sorrow for the Indonesian people, where the knights of KRI Nanggala 402 who died were the best sons of the nation and patriots who firmly had the duty to maintain the sovereignty of the country. Marine Matra Soldiers with military discipline, hierarchy, and honor have been proven physically and mentally by soldiers of KRI Nanggala 402 in carrying out their duties and responsibilities as soldiers of the Shark Kencana corps who have the motto "Wira Ananta Rudhiro" which means Persevere to the End. The sinking incident of KRI Nanggala 402 at a depth of 833 meters in the Bali Sea on April 21, 2021, the death of 53 of the best Indonesian Navy soldiers. The state has been present in an effort to resolve the sinking of KRI Nanggala 402 as a form of responsibility and respect for the fallen soldiers, especially the soldiers’ families. In accordance with Law Number 34 of 2004 concerning the Indonesian National Army (TNI), in resolving the rights of the families of soldiers who died by ensuring the survival of the families of soldiers of KRI Nanggala-402, including the assistance and attention of several countries that have given attention to the families of soldiers of KRI Nanggala- 402, as well as changes in the policies of TNI leaders, especially the Navy. Thus, this study is a descriptive-analytical study of the efforts and successes of the state to resolve the sinking incident of KRI Nangala-402 in the aspect of resolving the rights of families of soldiers who died in the line of duty and improving the submarine operational policy system in Indonesia.